Visual Outcome after Cataract Surgery in Phacomorphic Glaucoma in Tertiary Eye Care Centre in Western Nepal - Devkota, Prabhat Kiran; Khattri Chattri, Shital; Yogi, Anita; Pokhrel, Sushila; Khadka Thapa, Saraswati (Journal of Bharatpur Hospital, 2025)
Background Phacomorphic glaucoma is a preventable secondary glaucoma resulting from neglected cataract. This study evaluated the visual and intraocular pressure (IOP) outcomes after cataract surgery in patients diagnosed with phacomorphic glaucoma. MethodsA prospective observational study was conducted at Lumbini Eye Institute, Bhairahawa, Nepal, from August 1 to September 15, 2025, including 42 patients with phacomorphic glaucoma. All underwent comprehensive ophthalmic evaluation and manual small incision cataract surgery (SICS) with intraocular lens implantation. Pre- and postoperative visual acuity (VA), IOP, and complications were assessed. Statistical analyses were performed using SPSS version 16, with significance set at p-value